Diagnosis of Constipation in Family Practice - Simon Ferrazzi; Grant W Thompson; E Jan Irvine; Pierre Pare; Laureen Rance (Canadian Journal of Gastroenterology)
BACKGROUND: Patients who complain of constipation to their family doctor may not be truly constipated. Variability in stool frequency and consistency, and perception of symptoms may lead to inaccurate patient reporting or diagnosis of constipation.